Syrinx associated with intramedullary metastasis. Issue 8 (August 1987) - Foster, O; Crockard, H A; Powell, M P
Abstract : Two cases are reported of syrinx associated with an intramedullary metastasis. The first presented with hyperaesthesia in the right arm and bilateral pyramidal leg weakness, the second with a partial right sided Brown Sequard syndrome with a sensory level at D6. A possible pathological mechanism for the development of such syrinxes is discussed.